Protein expression patterns in HEK-blue-cells treated with Clinacanthus nutans extracts - Yang, Shun Kai; Leo, Teik Kee; Mai, Chun Wai; Chin, Swee Yee; Lamasudin, Dhilia Udie; Lim, Erin Swee Hua; Tan, Ngai Paing; Lai, Kok Song (Wolters Kluwer, 2020)
Background: Clinacanthus nutans (CN) is a small shrub native to tropical Asia known for their anti-oxidant, anti-inflammation, anti-cancer, and anti-viral activities. Objectives: This study aimed to investigate the effect of CN extract on human embryonic kidney cell line (HEK-Blue™-4) in a proteomic perspective. Materials and Methods: Comparative proteomic profiling through two-dimensional sodium dodecyl sulfate gel electrophoresis was performed on HEK-Blue™-4 treated with CN leaf polar extract. Results: We successfully identified seven upregulated proteins, of which five promoted the growth of the HEK-Blue™-4 cells. Interestingly, a potent antioxidant enzyme which neutralizes reactive oxygen or nitrogen species, peroxiredoxin-1 was also upregulated in HEK-Blue™-4 cell lines after treatment with CN leaf polar extract. Conclusion: CN leaf polar extract promotes the growth of HEK-Blue™-4 cells and induced the expression of peroxiredoxin-1, which protects the cells from reactive oxygen species during the inflammation process.